Accountability basis for decision-making - Gordon, Joe R. (Development Digest premier series, 1974)
Describes an approach for educators, librarians, and other professionals to use in designing, implementing, and adjusting programs to meet the goals and objectives set by the community. Applies the approach to a public school system in which the goals and objectives are set by the school board. The educational system creates, implements, and evaluates its total results in relation to the original goals and objectives. After conference, participants apply the approach in a workshop setting to their own problems, their results are discussed.